Impression management: the case of Malaysian financial graphs - Md Ali, Azham; Saad, Ram Al Jaffri (Universiti Utara Malaysia, 2006)
This Study investigates the use and abuse of graphs in the annual reports of 100 component stocks of the Kuala Lumpur Stock Exchange (KLSE)(now Bursa Malaysia) Composite index for the year 2001. It is found that 79% of companies use graphs and that 8.1 is the mean number of graphs per graph- using companies. The most commonly graphed financial variables are sales, profit, EPS and DPS. Column and bar graph types are more popular than line and pie graphs for both KFVs (Key Financial Variables) and non-KFVs Column and bar graphs account for 98% of KFVs and 75% of all graphs. However,line and pie graphs are more likely found for the non-KFVs than the KFVs.Though there is widespread use of graphs by Malaysian companies, available evidence point to the direction that Malaysian companies are not quite sophisticated users of graphs as their counterparts in the western developed countries such as the United States and Britain.This is especially clear when it concerns impression practices of selectivity and measurement distortion where the evidence is moderately supportive of studies overseas.This is perhaps expected considering the fact that the Malaysian stock market is not as strong as those in the United States and Britain.